The Analysis of Factor-factor That Affect The Safety Stock in Kapok Seed Oil Company - Andre Wijaya; Ryan Eleazar; Liem Gai Sin (AIBPM Publisher, 2018)
This research examines about analysis safety stock of Kapok Seed Oil in UD. Gajah Mas Company. The objectives of the research is to know the level of risk availability of raw materials and also stock for this Kapok Seed Oil processing in this company. Factor-factor research uses qualitative and secondary data, The data will be collected by interview and literatures review. The outcome is the analysis of that affect to safety stock in UD. Gajah Mas Company. Keywords : safety stock, kapok seed oil, qualitative data, secondary data, UD. Gajah Mas Company